Analysis of the financial management of the sukawarna public health center before and after becoming a regional public service agency - Rahmiyati, Ayu Laili (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The purpose of this study was to analyze the financial performance before and after BLUD based on the economic ratio value formula, efficiency and effectiveness of budget realization at UPTD Public Health Center Sukawarna. The research method used is the measurement of financial performance using economic, efficiency and effectiveness ratios. Data collection was conducted through interviews and a review of financial statement documents. The results of the analysis show that the economic ratio value at UPTD Public Health Center Sukawarna in 2020 (before BLUD), 2021 (BLUD transition period) and 2022 (after BLUD) is economical because it has an average economic ratio below 100%. The UPTD Public Health Center Sukawarna efficiency ratio value, it is inefficient because in 2022 (after BLUD) the efficiency ratio is inefficient or above 100%. The value of the UPTD Public Health Center Sukawarna effectiveness ratio is ineffective because in 2021 (BLUD transition period) and 2022 (after BLUD) the efficiency ratio is inefficient or below 100%. It is recommended that UPTD Public Health Center Sukawarna and UPTD Public Health Center Sukawarna maintain financial performance that has achieved good indicators in economic ratios and increase efficiency and effectiveness values by innovating, managing revenue, and prioritizing needs.